Matrix Based on the Second Derivative of Infinite Convergent Geometric Series - Lemma, Mulatu (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2017)
The infinite Geometric Series is a series of the form , where a is a constant. The geometric power series converges for and is equalto The Second Derivativeof Let tbe sequence in (0,1) that converges to 1.